2003
DOI: 10.1021/ar0300266
|View full text |Cite
|
Sign up to set email alerts
|

Analogies between Boron and Carbon

Abstract: The structural connections between the compounds of boron and carbon are extended using the mno rule beyond the borane-carbocation continuum, the lithium boride-polycarbyne analogy, and the magnesium boride (MgB(2))-graphite equivalence to beta-rhombohedral boron and fullerenes. The structural similarity of the pentagonal pyramidal C(6)H(6)(2+) and MgB(4) is established. An interesting electronic structural relationship between the B(84) fragment of the beta-rhombohedral boron and the fulleride anion, C(60)(12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
53
0
4

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(57 citation statements)
references
References 60 publications
0
53
0
4
Order By: Relevance
“…1 The transition from two-dimensional to three-dimensional structures is a notable feature of boron chemistry: in the solid state, for instance, MgB 2 is a superconductor 2 with a twodimensional graphite-like (honeycomb) boron layer separated by Mg atoms, MgB 4 is a three-dimensional system based on edge-shared pentagonal pyramides, 3 and MgB 6 is based on octahedral {B 6 } moieties. 4 Here it is noted that the similarity of pentagonal pyramidal [C 6 H 6 ] 2+ and the pentagonal pyramids in solid MgB 4 has been rationalised 5 by means of structural correlations between boron and carbon compounds. 6 Further, the pentagonal pyramidal motif is also that of the binary borane nido-B 6 H 10 , isoelectronic with the [C 6 H 6 ] 2+ dication.…”
Section: Introductionmentioning
confidence: 98%
“…1 The transition from two-dimensional to three-dimensional structures is a notable feature of boron chemistry: in the solid state, for instance, MgB 2 is a superconductor 2 with a twodimensional graphite-like (honeycomb) boron layer separated by Mg atoms, MgB 4 is a three-dimensional system based on edge-shared pentagonal pyramides, 3 and MgB 6 is based on octahedral {B 6 } moieties. 4 Here it is noted that the similarity of pentagonal pyramidal [C 6 H 6 ] 2+ and the pentagonal pyramids in solid MgB 4 has been rationalised 5 by means of structural correlations between boron and carbon compounds. 6 Further, the pentagonal pyramidal motif is also that of the binary borane nido-B 6 H 10 , isoelectronic with the [C 6 H 6 ] 2+ dication.…”
Section: Introductionmentioning
confidence: 98%
“…The polyhedral skeletal electron pair theory (PSEPT) has been exceedingly useful in categorizing clusters especially boranes and carbonys for many years (Mingos, 1972;Wade, 1976;Cox, 1981;Mingos, 1984;Lee, et al, 1989;Jemmis, et al, 1984;2002;2003;Balakrishnarajan and Hoffmann, 2004;Jemmis, 2005;Wales, 2005;Jemmis, et al, 2008;Welch, 2013). In our previous extensive work on clusters we found that the 4n and 14n rules could also be utilized to categorize the clusters and predict the shapes carbonyl cluster series (Kiremire, 2014;Kiremire, 2015a;Kiremire, 2015b) especially those of small to medium size level.…”
Section: Introductionmentioning
confidence: 99%
“…The Wade-Mingos rules have been extremely helpful in deducing the cluster geometries (Mingos, 1984;Wade, 1976;Jemmis, 1984Jemmis, ,2002Jemmis, ,2003Jemmis, ,2005Jemmis, ,2006Jemmis, ,2008King, 2002;Welch, 2013). Furthermore, it has been found that carbonyl clusters and some main group clusters can be categorized using 4n and 14n series (Kiremire, 2014(Kiremire, , 2015.…”
Section: Introductionmentioning
confidence: 99%